Development of low coast atmospheric pressure plasma jet for nano and bio technology applications - Rizon, Elfa Rizan (2018)
The development of cold atmospheric plasma (CAP) can overcome many limitations of low pressure plasma. Low temperature plasma is widely used in the semiconductor and medical industry for cleaning purposes. However, the process is time consuming because low pressure plasma requires vacuum environment. This renders the system unable to sustain continuous processes. Cold atmospheric plasma opened up new possibilities providing the ability to expose plasma to liquous samples, three-dimensional samples and enabling in-situ treatment. In this study several plasma configurations were constructed. The configuration that ignited stable plasma was the atmospheric pressure plasma needle jet (APPNJ). During optical measurements, energetic particles, Ar atoms, and other elements within the ultraviolet (UV) range such as secondary nitrogen, oxygen, and hydrogen were detected. The optimum treatment time, 60 s was obtained from several materials surfaces treated by APPNJ. Treatment time of 60 s, successfully enhanced surface wettability of microscope slide glass from 51.07° to 4.46°, polypropylene from 99.70° to 35.43°, and fluorine doped tin oxide from 59.06° to 9.9°. The wettability of Aluminium (Al) thin film was enhanced from 72° to 0°. The topography studies indicated that treated Al thin film surface roughness reduced by 2.86 X10-3 nm but the grain size was unaffected. The structural properties of the Al thin film showed no significant difference after plasma treatment, according to the full width at half maximum (FWHM) value of 111 orientations of Al thin films, both of which had the same value (0.3542 deg). The liquous sample of the Escherichia coli (E. coli) was exposed to direct (1.5 cm gap) and indirect (2.0 cm gap) plasma treatment. In the direct treatment, a total inactivation of E. coli was achieved after 100 s of plasma treatment. Indirect treatment of the same duration deactivated 54% of the bacteria. Overall, the purported abilities of CAP have been proved to be true and now await application in a variety of fields.